Implementasi Pendidikan Masyarakat Melalui Pemberdayaan Perempuan Berbasis Life Skill Education - Wayan Tamba; M A Rizka; Ika Andriani (Universitas Pendidikan Mandalika, 2020)
The purpose of this study is to describe the implementation of community education through empowering women based on life skills education in sewing at the Modes Kartini institution. This research method uses descriptive method with a qualitative approach. The method of determining research subjects using purposive sampling. Data collection techniques using observation, interviews, documentation. Analysis of research data using interactive analysis which includes data collection, data presentation, data reduction, drawing conclusions. The results of this study are the implementation of community education through the empowerment of women based on life skill education in sewing in the Modes Kartini Institute which has been carried out smoothly according to program technical guidelines. The impact of the program is that it can improve welfare, provide expertise and skills to women to be able to become entrepreneurs and improve the family economy.